The Boulton–Katritzky Reaction: A Kinetic Study of the Effect of 5‐Nitrogen Substituents on the Rearrangement of Some (Z)‐Phenylhydrazones of 3‐Benzoyl‐1, 2, 4‐oxadiazoles12. Issue 31 (24th September 2014) - Frenna, Vincenzo; Palumbo Piccionello, Antonio; Cosimelli, Barbara; Ghelfi, Franco; Spinelli, Domenico
Abstract: The kinetics of the ring‐into‐ring conversion of some new ( Z )‐phenylhydrazones of 3‐benzoyl‐1, 2, 4‐oxadiazole containing different nitrogen‐substituents at C‐5 (3b –d ; X = NHMe, NMe2, and NHCOMe) into the relevant triazoles4b –d have been examined in a wide range of p S + (0.1–11.9) in 1:1 (v/v) dioxane/water solution. The obtained results have been compared with previous data concerning the ( Z )‐phenylhydrazone of 5‐amino‐3‐benzoyl‐1, 2, 4‐oxadiazole (3a ; X = NH2 ). All of the studied ( Z )‐phenylhydrazones rearrange through three different pathways (specific acid‐catalysed, uncatalysed and general base‐catalysed). The different effects of the substituents on the course of the rearrangement in the three pathways have been examined. Abstract : The kinetics of the Buolton–Katritzky reaction of nitrogen‐substituted phenylhydrazones of 3‐benzoyl‐1, 2, 4‐oxadiazole to give the relevant triazoles have been examined in a wide range of p S + . The effect of substituents on three different pathways was elucidated.